From the Middle Ages to the 21st Century. Abortion, Assisted Reproduction Technologies and LGBT Rights in Argentina - Luna, Florencia (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
Despite "progressive" legislative changes concerning the LGBT collective and assisted reproductive technologies (ARTs) in Argentina, women and their sexual and reproductive rights have been overlooked. This article presents a critical perspective of some of these legislative modifications in the country. It addresses why some legislators and society are prepared to challenge a conservative or traditional approach for certain groups while ignoring others. Several factors are at play. There is no all-inclusive explanation. I stress that a striking double standard prevails in Argentina with respect to women and their sexual and reproductive rights. I also contend that powerful discrimination exists, in particular against poor women, who continue to suffer and are "punished" by the criminalization of abortion.